PEMANFAATAN TEMULAWAK DAN JAHE MERAH SEBAGAI FITOBIOTIK DAN PENGARUHNYA TERHADAP EFISIENSI NUTRIEN AYAM BROILER DI DAERAH TROPIS - Etha 'Azizah Hasiib; Edi Suryanto; Nanung Danar Dono (Wahana Peternakan, 2023)
ABSTRACT This study was conducted to know the use of turmeric (TRM) and red ginger meal (RGM) as source of phytobiotics green additive in the ration of broiler chickens dan the effect on nutrient efficiency. One hundred and eighty DOC male broiler chickens were randomly alloted into five dietary treatments in an opened-system poultry house. The five treatments were: basal diet without green additives supplementation (control; T1); control diet + 5g/kg TRM + 7.5 g/kg RGM (T2); control diet + 10 g/kg TRM + 7.5 g/kg RGM (T3); control diet + 5g/kg TRM + 15 g/kg RGM (T4); and control diet + 10 g/kg TRM + 15 g/kg RGM (T5). Each treatment was replicated 6 times with six birds in each replicate pen. Data obtained in this study were statistically analysed using One way classsification of variance analyses (RCBD). Result showed that supplementation of turmeric and red ginger in the ration did not show any significant effect on nutrient efficiency of broiler chicken. It might be concluded that when broiler chickens were raised under opened-system of poultry house, supplementation of turmeric and red ginger meal with the rate of 15 g/kg did not enough to nutrient efficiency of broiler chickens. Key words: Broiler chickens, Nutrient efficiency, Phytobiotic